Words are not all created equal: A new measure of ECB communication. (December 2017) - Picault, Matthieu; Renault, Thomas
Highlights: We develop a field-specific lexicon to quantify the content of ECB press conferences. We create two indicators measuring the monetary policy and the economic outlook. A term-weighting approach improves the quantification compared to benchmark measures. The measures help explaining future monetary policies, stock returns and volatility. To facilitate future research, the indicators are available atwww.cbcomindex.com . Abstract: We develop a field-specific dictionary to measure the stance of the European Central Bank (ECB) monetary policy (dovish, neutral, hawkish) and the state of the Eurozone economy (positive, neutral, negative) through the content of ECB press conferences. In contrast with traditional textual analysis, we propose a novel approach using term-weighting and contiguous sequence of words (n-grams) to better capture the subtlety of central bank communication. We find that quantifying ECB communication using our field-specific weighted lexicon helps to explain future ECB monetary decisions when considering an augmented Taylor rule. Regarding European stock market volatility, we find that markets are more (less) volatile on the day following a conference with a negative (positive) tone about the euro area economic outlook. Our indicators significantly outperform a textual classification based on the Loughran–McDonald or Apel–Blix Grimaldi dictionaries and a media-based measure of economic policy uncertainty.